Quantitative Trait Loci Mapping and Marker Identification for Low Salinity Tolerance Trait in the Swimming Crab (Portunus trituberculatus) - Lv, Jianjian; Sun, Dongfang; Yan, Deping; Ti, Xingbin; Liu, Ping; Li, Jian (Frontiers in Genetics, 2019)
Low salinity is one of the most important abiotic factors that directly affect the abundance of the swimming crab, Portunus trituberculatus. Quantitative trait loci (QTL) mapping will be helpful in identifying the markers and genes involved in low salinity tolerance. In this study, QTL mapping was performed based on a high-density linkage map. Two QTLs of low salt tolerance were mapped on one linkage group (LG) (LG17, 2.6-5.2 cM). Five low salinity-related markers were found at the family level and one of those markers was closely related to low salinity tolerance at the population level. Twenty-four low salt-related candidate genes (including DNA mismatch repair protein, aldehyde dehydrogenase, and glucosyltransferase) were identified. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses suggested that four pathways may be associated with low salinity tolerance. This represents the first report of QTL mapping for low salinity tolerance in the swimming crab, which will be useful to elucidate salinity adaptation mechanisms.